From the EDVAC to WEBVACs. - WANG, DANIEL C. (Communications of the ACM, 2015)
The article explores some of the fundamental issues related to cloud computing. Topics discussed include many components of a cloud computer that systematically deal with the failure of those components, a common architectural pattern used to manage transient failures and the use of simple analytic techniques to allow quantitative statements. Also provided are approaches to addressing frequent server-level failures in a data center, including the decomposition of the system into one or more tiers of servers.